Understanding the Child’s Mind in Marital Conflict: A Comparative Psychological Study - Nazir, Sehrish; Sengupta, Saptarshi (Journal of Neonatal Surgery, 2025)
Marital conflict is a widespread problem that not only impacts the dynamics of spousal relationships but also has serious psychological effects on children. This comparative psychological study investigates how different levels of marital disputes influence children's mental health, focusing on behavioral, emotional, and cognitive aspects. The present study uses a sample of children from both high-conflict and low-conflict family settings. In addition that study applies standardized psychological assessments to measure anxiety, depression, self-esteem, and behavioral adjustment. The findings show a strong link between the severity of parental conflict and worsening child mental health outcomes, highlighting the urgent need for early intervention and family-focused psychological support.